The Role of Entrepreneurial Marketing in Strengthening Brand Image of E-Commerce SMEs: A Systematic Literature Review - Aggi Panigoro Sarifiyono; Elan Rusnendar; Anang Bambang Pujianto; Sabilla Saberina; Susan Purnama; Rizki Gilang Fernando; Johnson Sinaga (CAKRAWALA : Management Science Journal, 2026)
This study identifies entrepreneurial marketing strategies that enhance brand image in e-commerce SMEs through a systematic literature review (SLR) of 73 Scopus-indexed articles published between 2015 and 2024. Using thematic analysis and narrative synthesis, the study uncovers three key mechanisms: integration of entrepreneurial and market orientations, creation of emotional connections through social media, and development of brand management capabilities. Customer focus and emotional engagement are the strongest drivers of brand image, supported by digital technologies such as e-commerce platforms, artificial intelligence, and social media marketing. The effectiveness of these strategies is influenced by organizational readiness, market turbulence, competitive intensity, cultural context, and owner-manager characteristics. Research gaps remain in integrating entrepreneurial marketing and brand management frameworks, reliance on cross-sectional studies, and limited understanding of brand articulation capabilities. Practically, enhancing organizational readiness and strategic digital adoption are essential to optimize entrepreneurial marketing’s impact on brand image and competitiveness in e-commerce SMEs.